The Effect Of Price And Facilities On Staying Decisions At Grand Mercure Maha Cipta Medan Angkasa Hotel - Manao, Asri Rindiani; Edi Winata (SEAN Institute, 2024)
The pupose of this study was to determine whether there is an effect of price and facilities on the choice of guests who stay. The sample of this study were 98 visitors who visited the Grand Mercure Maha Cipta Medan Angkasa Hotel in April-May 2024, sampling using the accidental sampling method, namely anyone who accidentally meets the researcher can be used as a sample, if it is deemed that the person who happened to be met is suitable as a data source. Data analysis uses Multiple Linear Regression tests, while data processing uses SPSS. The results showed that partially price had an effect on staying decision, facilities also had a positive and significant effect on staying decision, while simultaneously price and facilities had a positive and significant effect on staying decision.